RAISING THE MARRIAGE AGE, RAISING DISPENSATIONS? EVIDENCE FROM THE MALANG RELIGIOUS COURT AFTER CONSTITUTIONAL COURT DECISION NO. 22/PUU-XV/2017 - Arifah, Risma Nur; Hussin, Mohd Nurhusairi Bin Mat; Rahmawati, Erik Sabti; Zahro, Anggreani Kharimatuz (Universitas Nurul Jadid, 2025)
This study examines the legal consequences of Constitutional Court Decision No. 22/PUU-XV/2017 on the minimum marriage age and its relationship with the rising number of marriage dispensation cases before the Malang Religious Court. Using an empirical juridical (socio-legal) approach, primary data were collected through interviews with judges and court clerks, while secondary data comprised relevant statutes, the Constitutional Court decision, and selected court rulings. The findings indicate that the decision was accommodated through Law No. 16 of 2019, which equalized the minimum marriage age at 19; however, implementation has redirected practices toward the dispensation mechanism. SIPP data show a sharp increase in dispensation petitions in the Malang City Religious Court (83 in 2018; 183 in 2019; 260 in 2020; 261 in 2021). Key constraints include open-textured dispensation standards, weak operational guidance and cross-sector coordination, the voluntary nature of proceedings, and broad judicial discretion that normalizes dispensations. Policy recommendations include tightening “urgent reasons” criteria, issuing stricter judicial guidelines, and requiring health-psychological assessments and child-protection involvement.